High-power single-wavelength SOA-based fiber-ring laser with an optical modulator - Ooi, H.C.; Ahmad, Harith; Sulaiman, Abdul Hadi; Thambiratnam, Kavintheran; Harun, Sulaiman Wadi (IOP Publishing, 2008)
A semiconductor optical amplifier (SOA) fiber-ring laser (SOAFRL) utilizing a fiber-Bragg grating (FBG) and lithium niobate (LiNbO3) modulator is demonstrated. The laser operates at a wavelength of 1547.64 nm, which is equal to the Bragg wavelength in the saturation region. By removing the LiNbO3 modulator in the ring, the laser shows a single-wavelength output, which has a lower peak power. The experimental results show that when reaching the saturation level, the system with the LiNbO3 modulator shows a higher saturation current and peak power compared to that of the system without the modulator. The effect of varying the modulation frequency on the laser output power is investigated. By incorporating the LiNbO3 modulator in the laser cavity, the side-mode suppression ratio (SMSR) of the laser is significantly improved and a higher peak power can be obtained at a higher current.